Basic guidelines for high-fidelity medical simulation - Studnicka, Katarzyna; Zarzycka, Danuta; Dziura, Małgorzata; Kijowska, Agnieszka (Journal of Education, Health and Sport, 2018)
Introduction Simulation based medical education is an increasingly popular pedagogical approach. It provides students with the opportunity to practice their clinical skills and decision-making through various simulation activities. The main purpose of medical simulation is to educate and improve patient safety. The aim. Presentation of the basic guidelines for the implementation of medical simulation methods in the education of nurses. The method. Non-systematic review of literature, based on a thematic selection of articles with a preference for the studies being systematic reviews of papers published in the last 13 years. Results.Based on the review of the literature on SBME covering the period from 1969 to 2003 and from 2003 to 2009 Mc.Gaghie and the co-authors present twelve features and best practices for effective medical education based on simulation. The authors of this study found them to be fundamental for the development of this method and for forming and improving medical competences. Summary.Medical Simulation in education is a very important step on the way of gaining key competences in team work and decision-making skills. It is also a complementary training to many methods and educational strategies, but it will not substitute the training in natural conditions of in-patient care and professional experience arising from this.